High Value Care Cost conscious: practicing habits and awareness among the doctors during clerkship - Talib Hussain, Ashfaq Hussain, Sohail Hameed, Muhammad Arshad, Mazhar Ul Haque, Farheen Hameed (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the high value care cost conscious awareness among post administrative staff and doctors clinical. Study design: Cross sectional Survey. Place and duration of study: Shahida Islam Medical and Dental College and Hospital. From Jan 2021 to Dec 2021 Methodology: 50 doctors were recruited for conducting the proposed study and asked them to fill the questionnaire i.e., Maastricht HVCC Attitude Questionnaire (MHAQ) which was divided into three subscales such as high-value care, cost incorporation and perceived drawbacks. Moreover, job demands, and resources related questions were asked to resident respondents followed by the assessment of other stakeholders’ HVCCC attitudes. Data was analyzed using univariate and multivariate analyses. Results: Following results have been noted during the research: HVCCC attitudes of faculty and administrators have been more positive than residents (p ≤ 0.05) whereas patients showed less positive behavior (p ≤ 0.05) than residents. Moreover, residents’ understanding for the HVCCC attitudes of faculty and patients was underestimated (p < 0.001) and overestimated (p < 0.001) respectively. It was observed that the increasing age was directly proportional to the positive attitudes towards HVCCC in both residents and faculty (p ≤ 0.05). While in patients’ lesser positive attitudes towards HVCCC was significantly associated (p < 0.001) with lower perceived health quality. Direct relationship of the autonomy of residents perceived with their attitudes towards the HVCCC was also observed i.e., more independence means more positive attitudes. Conclusions: Attitudes towards HVCCC of the residents during course of residency vary due to their behavior and learning environment. Residents might misinterpret the faculty’s attitudes and patients attitudes as well. Faculty and administrators must be more supportive towards residents to enhance their capabilities through their experiences and knowledge of HVCCC and by giving them freedom in clinical practice.